2012
DOI: 10.5005/jp-journals-10028-1040
|View full text |Cite
|
Sign up to set email alerts
|

Does the Excessive use of Mobile Phones in Young Adults Reflect an Emerging Behavioral Addiction?

Abstract: Background and objective: Mobile phones have become an essential part and parcel of modern life. Some of the studies have shown potentially adverse consequences of excessive mobile phone use. Aim of this study was to explore the pattern of mobile phone use among young adults and evaluate the mobile phone use pattern on the substance dependence criteria and assess the adverse consequences of mobile phone use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Previous research across both qualitative and quantitative research also identified the capability of smartphones in providing this pacifying psychological distraction (Ariel et al, 2017;Gauld et al, 2016;Grellhesl & Punyanunt-Cater, 2012;Lapointe et al, 2013;Panova & Lleras, 2016;Wang et al, 2015). From this, it may be possible to infer that, for the purpose of coping with unfavourable situations, problem smartphone use may be influenced by the "security blanket" hypothesis (Panova & Lleras, 2016) in which smartphones are demonstrating to provide (Nehra et al, 2012). Adopting this approach manifests ' avoidance coping', which research has argued is an unhealthy way to handle problem situations (Demirci, Akgonul, & Akpinar, 2015;Grellhesl & Punyanunt-Carter, 2012;Nehra et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research across both qualitative and quantitative research also identified the capability of smartphones in providing this pacifying psychological distraction (Ariel et al, 2017;Gauld et al, 2016;Grellhesl & Punyanunt-Cater, 2012;Lapointe et al, 2013;Panova & Lleras, 2016;Wang et al, 2015). From this, it may be possible to infer that, for the purpose of coping with unfavourable situations, problem smartphone use may be influenced by the "security blanket" hypothesis (Panova & Lleras, 2016) in which smartphones are demonstrating to provide (Nehra et al, 2012). Adopting this approach manifests ' avoidance coping', which research has argued is an unhealthy way to handle problem situations (Demirci, Akgonul, & Akpinar, 2015;Grellhesl & Punyanunt-Carter, 2012;Nehra et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…From this, it may be possible to infer that, for the purpose of coping with unfavourable situations, problem smartphone use may be influenced by the "security blanket" hypothesis (Panova & Lleras, 2016) in which smartphones are demonstrating to provide (Nehra et al, 2012). Adopting this approach manifests ' avoidance coping', which research has argued is an unhealthy way to handle problem situations (Demirci, Akgonul, & Akpinar, 2015;Grellhesl & Punyanunt-Carter, 2012;Nehra et al, 2012). Therefore, future health psychology promotion could aim to alert smartphone users of the adverse outcomes of using one's smartphone to avoid psychological discomfort, such as potential increases in social anxiety (Elhai, Tiamiyu & Weeks, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study in India showed that the rate of cell phone addiction was33.33% among teenagers (49). A survey done by Nehra et al indicated that the rate of cell phone addiction among adults was reported from 33.5% to 39.6% (50). One of the factors contributing to the increase of this dependency is the hardware and software of cell phone, because these features are used as an access to information, education, entertainment, games, news, photography, videos and communications.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also studied the relationship between smartphone use and addiction (Haug et al. , 2015; Choliz, 2010; Nehra et al. , 2012; K Abhari and Vaghefi, 2022; Vaghefi et al.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Scholars have studied predictors of smartphone addiction, including time of daily use, time of use after waking up (Haug et al, 2015), preference for social interaction, emotional lift, ease of use and flow (Lee and Shin, 2016), understanding, orientation and communication dependence (Li and Lin, 2018), loneliness (Mahapatra, 2019), self-regulation (Mahapatra, 2019;Abhari et al, 2021) and need to connect socially (Roberts et al, 2014). Research has also studied the relationship between smartphone use and addiction (Haug et al, 2015;Choliz, 2010;Nehra et al, 2012;K Abhari and Vaghefi, 2022;Vaghefi et al, 2017;Loid et al, 2020). In addition, the consequences of smartphone addiction have been investigated, including assessment of smartphone addiction (Kwon et al, 2013b;Lapointe et al, 2013), job-related outcomes (Bian and Leung, 2015;Lee and Shin, 2016), psychological outcomes (Samaha and Hawi, 2016;Moqbel, 2020) and smartphone addiction effects on family, personal and academic conflicts (Mahapatra, 2019).…”
Section: Literature Review and Theoretical Foundation 21 Smartphone A...mentioning
confidence: 99%